The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/19401736.2014.987269
|View full text |Cite
|
Sign up to set email alerts
|

Linking eggs and adults of Argulus spp. using mitochondrial DNA barcodes

Abstract: We have created barcode library for common Argulus spp. infecting Carassius auratus, which could also be used to identify premature forms of Argulus spp. even by non-professionals. Infected C. auratus was examined and purchased from ornamental fish-trading centers and the adult life stage of Argulus spp. was identified and DNA barcoded. The eggs of Argulus spp. were collected using bottle implants. The collected eggs are barcoded and precisely identified by matching with the adult sequences. Four species of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In contrast, the maximum genetic distances present for A. japonicus and C. hyperboreus are 0.366–0.981 for single PCG datasets and 0.641 for concatenated PCG datasets, once again confirming that A. japonicus was closely related to A. americanus but diverged from C. hyperboreus ( 57 ). Comparisons of genetic distance structures showed that the values of the cox1-based K2P genetic distances were all significantly smaller than those of other single PCG and concatenated PCGs, in agreement with the aforementioned result, in which the cox1 was regarded as the most conserved gene among crustacean species ( 29 ). Perhaps this conclusion can be further validated when additional crustacean mitogenomes become available, especially from the genus Argulus .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, the maximum genetic distances present for A. japonicus and C. hyperboreus are 0.366–0.981 for single PCG datasets and 0.641 for concatenated PCG datasets, once again confirming that A. japonicus was closely related to A. americanus but diverged from C. hyperboreus ( 57 ). Comparisons of genetic distance structures showed that the values of the cox1-based K2P genetic distances were all significantly smaller than those of other single PCG and concatenated PCGs, in agreement with the aforementioned result, in which the cox1 was regarded as the most conserved gene among crustacean species ( 29 ). Perhaps this conclusion can be further validated when additional crustacean mitogenomes become available, especially from the genus Argulus .…”
Section: Resultssupporting
confidence: 84%
“…For example, nuclear genetic markers, including small ribosomal protein 18 (18S), OPC19, and OPH11, have been employed to explore the genetic diversity and species identification of Argulus parasites (6,19,26,27). Moreover, the mt genes, such as cox1, nad1, and nad4, have also proven effective for Argulus identification because of their matrilineal inheritance, high copy number, lack of recombination, and rapid evolution (28)(29)(30)(31). However, compared to single or partial genetic loci, a complete mt genomic dataset would be especially powerful for displaying sufficient interspecies variability and describing species specificity (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…The thorax has four segments, each having a pair of swimming legs and abdomen has a bilobed segment (Mirzaei et al, 2015). The diverse morphological adaptation of Argulids has taxonomic significance and low host specificity which makes them potent ectoparasites (Feroz et al, 2014) for many important cultivable species. The severity of these ectoparasites is reflected with its direct pathological impacts in host coupled with co-infections, mostly secondary infections.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate identification of species is fundamental requirement in any studies and traditionally species are identified using morphological characters (Shashank et al, 2014). Even though conventional morphological keys exist for ichthyoparasites, it is very complicated to define such morphological keys for smaller crustaceans like Argulus species (Feroz et al, 2014). To address this difficulty, molecular approaches like DNA barcoding offer great promise for precise identification of species of all life stages.…”
Section: Introductionmentioning
confidence: 99%